Neurocognitive Outcome and Compensating Possibilities in Children and Adolescents Treated for Acute Lymphoblastic Leukemia With Chemotherapy Only - Lofstad, Grete Elisabeth; Reinfjell, Trude; Weider, Siri; Diseth, Trond H.; Hestad, Knut (Frontiers in Psychology, 2019)
Aim: To examine the neurocognitive outcomes in children and adolescents with Acute Lymphoblastic Leukaemia (ALL) in remission who were treated with central nervous system prophylactic chemotherapy only (CTO). Methods: Neurocognitive performances in 36 children and adolescents, aged 8.4 - 15.3 years, in long-term remission from ALL, 4.3 -12.4 years post diagnosis, without relapse and with no pre-diagnosis history of neurodevelopmental disorder, were compared with those of 36 healthy controls matched for gender, age and parents’ socio-economic status. The former patients and the healthy controls completed an extensive battery of standardized neuropsychological tests. Results: Survivors who were treated by CTO obtained significantly lower scores than healthy controls on the domains of tactile sensory function, abstraction, processing speed, arithmetic, copying and drawing. The ALL survivors exhibited a steeper rising learning slope, with lower scores after single-trial memory and problem-solving tasks, but caught up with the controls when the stimuli were repeated. Conclusion: The results indicate that neurocognitive long-term sequelae in ALL survivors is limited to specific domains, particularly arithmetic, complex drawing, tactile processing and processing novelty. Intervention programs and school programs should account for this deficit in processing new information and taking advantage of repetitions as a strength may prevent survivors from falling behind their peers.